Lift the Flap Book Media Affect Disaster Preparedness in Early Childhood - Ulfah, Karima Ulya; Rolina, Nelva; Alfina, Cut Sarna (Universitas Pendidikan Ganesha, 2024)
Children are still not aware of the dangers of disasters; knowledge of preparedness is still lacking. Another problem is that children don't know exactly what to do before, during, or after a disaster. This research aims to analyze the influence of using the lift the flap book media